"Love" the Local, "Use" the National, "Study" the Foreign: Shifting Javanese Language Ecologies in (Post‐)Modernity, Postcoloniality, and Globalization. (December 2014) - Zentz, Lauren
Abstract : Indonesian state development policies have shaped definitions of language, meanings conveyed through language, and access to language forms through deliberate policy actions that pervade public, and increasingly, private life. Modern language ideologies that are part and parcel of national development have informed these policies and informed educated youths' understandings and rationalizations of their linguistic competencies. In this paper I explore how macro‐level language policies informed by modern language ideologies and micro‐level influences in the form of peer pressure and adult shaming encourage shift toward the national language, Indonesian, and away from Javanese. State policies advising citizens to "love" their local languages, but "use" their one national language, Indonesian, work together with micro‐level social interactions to nudge language shift in the direction of an increasingly monolingual, Indonesian‐speaking populace.